EKSPLORASI FAKTOR YANG MEMPENGARUHI PESERTA DIDIK DALAM MENGAMBIL KEPUTUSAN PEMILIHAN STUDI LANJUT (Studi pada Peserta Didik Kelas XI di SMAN 15 Padang) - Fadrila Ramadhani; Rahma Wira Nita; Rila Rahma Mulyani (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study was motivated by the fact that students are unaware of their potential in terms of further study options. The objectives of this study are: 1) to identify the factors that influence students in making decisions about further study options from internal factors, 2) from external factors that influence students in making decisions about further study options. The type of research used is a quantitative descriptive method. The study population consists of 320 students. The sample was selected using simple random sampling, resulting in 92 respondents. Data collection was conducted using a questionnaire with interval data analysis. Based on the research results, it was found that 1) Internal factors influencing students in making decisions about further education are numerous, including intelligence, knowledge, special talents, interests, and life values. 2) External factors influencing students in making decisions about further education are numerous, including family socioeconomic status, education, community, peers, and extended family influence. Based on the research findings, it is recommended that guidance counselors develop comprehensive and responsive counseling services tailored to students' needs. Guidance counselors should provide structured information about educational pathways and career prospects, as well as implement career counseling services based on interests and talents.